An Assessment of Health-Economic Burden of Obesity Trends with Population-Based Preventive Strategies in a Developed Economy - Prerna Bhasin (Intelektual Pustaka Media Utama, 2017)
The burden of obesity varies with age, ethnicity, socio-economic status and state economies. All new projections should hence accommodate population ageing, and other population changes such as immigration, health-care system reform, or technological advances for disease treatment for a comprehensible assessment of global burden. The unfordable and expensive nature for reversing the obesity tide arises from policies developed to combat obesity. Most of these approaches aim at bringing the problem under control, rather than affecting a cure, and obviously require a multi-disciplinary and intensive regimen. Prevention is the only feasible option and is essential for all affected countries. Yet it is not simple to have population based UK-wide strategic framework for tackling obesity. Besides existence of multiple layers of governance, there are clear demarcations between targets in diet; nutrition and physical activity level between regions some of which are not realistic. Population based approaches target policies and process, aiming for a transition towards healthy population diets, activity levels and weight status. It is essential to understand these aspects differ culturally and between and within countries. There are still no clear and appropriate answers about answer when, where, why, and, how costs accrue in obese populations, further long term commitments are required for the same. Most population-based prevention policies are cost effective, largely paying for themselves through future health gains and resulting reductions in health expenditures. Therefore these prevention programs should be high on the scientific and political agendas.